Estimation of Pinus pallasiana D. Don to the conditions of technogenic environmental pollution in steppe plantations of Ukraine - Korshykov, I.I.; Terlyga, N.S.; Bytchkov, S.A.; Mazur, A.E. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
25–30 year old trees of Pinus pallasiana D. Don were observed in 8 plantations situated in different polluted rural and urban zones of Kryviy Rig and Azov regions. A new scale for conifer life duration was developed. High hardiness of Pinus pallasiana D. Don to technogenic environment pollution was shown.